Current methodologies on genotyping for nosocomial pathogen methicillin-resistant Staphylococcus aureus (MRSA). (June 2017) - Miao, Jian; Chen, Lequn; Wang, Jingwen; Wang, Wenxin; Chen, Dingqiang; Li, Lin; Li, Bing; Deng, Yang; Xu, Zhenbo
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a common pathogen in hospitals and the community. As the rapid spread and wide distribution of antimicrobial resistance (such as MRSA), treatment for infectious diseases caused by microorganisms has become a vital threat. Thus, early identification and genotyping are essential for further therapeutic treatment and the control of rapid expansion of MRSA. In combination with applications and data feedbacks, this review focused on the currently available molecular-based assays on their utility and performance for rapid typing of MRSA, especially on effective molecular-based methods. Besides, a common mobile element SCC mec and prevalence of HA-MRSA, LA-MRSA and CA-MRSA were introduced in this review in order to provide a more complete profile of MRSA. Highlights: A comprehensive review for MRSA genotyping which contained various methods. Informative and numerous appliance and data feedback were conducted into this review. The joint of some relevant supplements such as SCC mec and integron enriched this review.